Upliftment of Spirituality and Its Impacts on The Life of Muslim - Sani Hamisu; Aishatu Abubakar Kumo (Research Synergy Foundation, 2024)
Islamic spiritual upliftment is a transformative journey that purifies the soul, aligns with divine guidance, and fosters a personal relationship with Allah. This study aimed to explore the techniques and impacts of spiritual upliftment in Islam, providing insights for the Muslim Ummah to enhance their spiritual growth. Using a qualitative approach with an analytical descriptive method, we reviewed 25 publications from 2015 to 2022, including books, articles, and online materials. Our findings revealed that embracing Islam guidelines and teachings, such as prayer, repentance, Qur'an recitation, remembrance of Allah, and ethical conduct, leads to inner tranquillity, resilience, a deeper connection with the Creator, and contentment despite external circumstances. Our study highlights the importance of tawhid (oneness with Allah), worship, and ethical conduct in achieving spiritual upliftment. This review provides a comprehensive understanding of Islamic spiritual upliftment, guiding Muslims to cultivate a stronger connection with Allah and embody excellence, responsibility, compassion, and social justice.